Mendukung Sustainable Development Goals; Studi Literatur Kebijakan Sistem Pendidikan China, Finlandia, Jepang, dan Indonesia - Septaria Dinda Serena; nurul chasanah; Auliya, Indi (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to identify in several countries related to education system policies that are pro SDGs, especially related to quality education, as well as to identify existing education system policies in Indonesia related to SDGs. This research method is literature by quoting from various reference sources of websites, books, journals consisting of international journals, Sinta journals, and Jenius journals. The 2012 UN Summit produced a renewal called the Sustainable Development Goals (SDGs). There are 17 goals formulated, one of which is related to quality education. Quality education around the world requires absolute education policies to support it. Countries such as China, Finland, Japan, and Indonesia have shown that they support the SDGs on quality education and have their own education policies. Japan has a track record of implementing policies that support the SDGs, including the provision of free education ranging from pre-primary to tertiary education. While Finland, SDGs are one of the seven themes emphasized in the main education curriculum. China's education policy aims to align educational efforts with social and personal resources and improve the quality of education of citizens. Indonesia's policies, among others, aim to increase access to quality education, improve the quality of teachers, education support organizations, improve education services, strengthen, and develop human education with character.